Solvent‐Promoted Regio‐ and Stereoselectivity in Ru‐Catalyzed Hydrocarboxylation of Terminal Alkynes: A DFT Study. Issue 3 (19th December 2017) - Maity, Bholanath; Koley, Debasis
Abstract: DFT calculations at the M06L‐D3(SMD)/LANL2TZ(f)/6‐311+G(d, p)//M06L/LANL2DZ/6‐31G(d)* level were performed to explore the mechanism, solvent effect, and origin of selectivity in the hydrocarboxylation of terminal alkynes catalyzed by (PCy3 )2 (CO)RuHCl. This catalytic system offers a unique example in which selectivity in enol‐ester synthesis is controlled in presence of different solvent media under mild reaction conditions. In CH2 Cl2 solvent the regioselective gem ‐enol‐ester (P g ) was preferred, whereas stereoselective Z ‐enol‐ester (P Z ) was observed exclusively in THF medium. We have unraveled the complete catalytic mechanism involving the following steps: a) alkyne coordination with subsequent nucleophilic attack and, finally, b) product elimination leading to the Markovnikov productP g in both solvent media. Herein, the rate‐limiting nucleophilic attack step requires an activation barrier of 20.5 ( 21.0 ) kcal mol −1, which is 5.7 ( 5.6 ) kcal mol −1 lower than the crucial vinylidene formation step encountered for anti‐Markovnikov addition. Interestingly, a new reaction avenue unfolds under explicit THF medium, in which the inherent coordinating nature of the solvent becomes effective in altering the product regioselectivity. Under such an event, a highly facile ligandassisted proton shuttle (LAPS) mechanism is propagated, leading to vinylidene complex11A . This intriguing mechanistic scenario facilitates favorably furnishing theP Z product rather than theP g isomer by 4.3 kcal mol −1 . Abstract : Solvent effects on selectivity : The product selectivity in the hydrocarboxylation of terminal alkynes in the presence of different solvent environments is explored by means of a theoretical approach. In CH2 Cl2 medium, Markovnikov addition become facile, whereas in THF medium the anti‐Markovnikov Z ‐product is preferred via a facile vinylidene intermediate.